ANALYSIS OF IMMATURE PLATELET FRACTION AND MEAN PLATELET VOLUME IN ACUTE CORONARY SYNDROME PATIENT - Pratia Paramita; Asvin Nurulita; Ruland DN Pakasi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Platelets have a central role in the pathogenesis of ACS. Immature Platelet Fraction (IPF) considered as a potential marker of the platelet activation process and platelet turnover process. Immature platelets have greater prothrombotic potential and aggregate more rapidly with collagen that affects platelet hemostasis potential that may contribute to the formation of thrombus. Therefore IPF is associated with the progression of coronary heart disease. MPV values reflect platelet activation. A cross sectional study was held in the clinical pathology laboratory of Dr. WahidinSudirohusodo Hospital Makassar during September-November 2016. 67 samples underwent and declared ACS by the physician. 67 patients with ACS were involved with a distribution of 30 patients STEMI (44.8%), 30 patients NSTEMI (44.8%), and 7 patients UAP (10.4%). Subjects are mostly male (73.1%) and young adult age (82.1%). There was significant difference of IPF value especially in STEMI group with mean 3,1 (p = 0,004) and no significant difference of MPV value in ACS group.Pearson correlation test showed there was positive correlation with weak strength of IPF and MPV values in ACS patients (p = 0.02, r = 0.388). There was a significant difference between IPF scores according to GRACE score (p = 0.005). Increased IPF value in STEMI group. The IPF score can be considered as a risk stratification of ACS patients replacing GRACE score. There was a positive correlation with weak strength of IPF and MPV value in ACS patients.